Prospective Study of 2 Bed Alarms for Detection of Nocturnal Seizures. (November 2013) - Fulton, Stephen; Poppel, Kate Van; McGregor, Amy; Ellis, Michelle; Patters, Andrea; Wheless, James
For parents of children with epilepsy, seizures occurring in sleep are a major concern. Risk factors for sudden unexplained death in epilepsy patients include being in bed and generalized tonic-clonic seizures. A device for detecting nocturnal seizure activity would be valuable. Children with various seizure types undergoing evaluation had standard video electroencephalography (EEG), cardiopulmonary and nursing monitoring, and 1 of 2 models (ST-2 and MP5) of a Medpage bed alarm. The video EEG record was reviewed to detect any seizures missed by the bed alarms or caregivers. The ability of the bed alarms to detect motor seizures in general and specific seizure types was tested. In 15 patients, 69 seizures were recorded by video EEG. The ST-2 did not detect any nocturnal seizures. The MP5 alarm detected 1 of 15 in sleeping patients: a generalized tonic-clonic seizure. The Medpage seizure alarms do not appear to adequately detect nocturnal seizures.